MODEL WISATA HALAL BERBASIS KOMUNITAS - Atang Abd. Hakim; Uu Nurul Huda; Rohmanur Aziz (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2019)
Halal Tourism in Indonesia, now is becoming a brand for attractive types of tourism to be developed. Halal tourism is an effort to flexibility Islamic law in the practical context of the current lifestyle that integrates the values of halal and thoyyib (good) to the tourism sector in order to improve the economy of the community. Halal Tourism Village is a tourist village that offers the nuances of religiosity that are included in your aspects of tourism in life based on shari'ah principles. Cibuntu as a village established by the Kuningan Regency Government as a Tourism Village has the potential to be developed into a halal tourism village. This mentoring activity uses the PAR method (Participatory Action Research) which has three key variables, namely, Participatory (involvement), Action (service action) and Research (research). The results of these activities include: first, the political awareness of the village government, stakeholders of Kompepar (the Driving Group of Tourism), the Cibuntu Village Community in building and developing the potential of historical tourism, natural tourism and agro tourism into halal tourism destinations. This awareness has begun with the drafting of the Peraturan Desa draft on the development of the halal village of Cibuntu village; second, community empowerment in managing the Natural Resources and Human Resources of the Cibuntu Village is ready to realize a halal tourism village; third, the emergence of local government attention to the development of the Cibuntu Village community by building the Cibuntu Village Empowerment Halal as a place of discussion and consultation between parties involved in the Cibuntu Village Community